Expression of the Concept of "Perseverance" in the Text of The Documents - Jamoliddinova Iroda Bahodir kizi (Scientific Trends, 2024)
Information about the expression the concept of “perseverance” by various means in the formal style. In particular, in the text of documents in the Uzbek language, perseverance is illuminated by lexical, grammatical, graphic means.
Keywords: Concept, concept” perseverance